S100B protein level for the detection of clinically significant intracranial haemorrhage in patients with mild traumatic brain injury: a subanalysis of a prospective cohort study. Issue 4 (18th December 2020) - Blais Lécuyer, Julien; Mercier, Éric; Tardif, Pier-Alexandre; Archambault, Patrick M; Chauny, Jean-Marc; Berthelot, Simon; Frenette, Jérôme; Perry, Jeff; Stiell, Ian; Émond, Marcel; Lee, Jacques; Lang, Eddy; et al.
Abstract : Background: Clinical assessment of patients with mild traumatic brain injury (mTBI) is challenging and overuse of head CT in the ED is a major problem. Several studies have attempted to reduce unnecessary head CTs following a mTBI by identifying new tools aiming to predict intracranial bleeding. Higher levels of S100B protein have been associated with intracranial haemorrhage following a mTBI in previous literature. The main objective of this study is to assess whether plasma S100B protein level is associated with clinically significant brain injury and could be used to reduce the number of head CT post-mTBI. Methods: Study design: secondary analysis of a prospective multicentre cohort study conducted between 2013 and 2016 in five Canadian EDs. Inclusion criteria: non-hospitalised patients with mTBI with a GCS score of 13–15 in the ED and a blood sample drawn within 24 hours after the injury. Data collected: sociodemographic and clinical data were collected in the ED. S100B protein was analysed using ELISA. All CT scans were reviewed by a radiologist blinded to the biomarker results. Main outcome: the presence of clinically important brain injury. Results: 476 patients were included. Mean age was 41±18 years old and 150 (31.5%) were women. Twenty-four (5.0%) patients had a clinically significant intracranial haemorrhage. Thirteen patients (2.7%) presented a non-clinically significant brain injury. A total of 37 (7.8%) brain injured patients were included in our study. S100B median value (Q1–Q3) was: 0.043 µg/L (0.008–0.080) for patients with clinically important brain injury versus 0.039 µg/L (0.023–0.059) for patients without clinically important brain injury. Sensitivity and specificity of the S100B protein level, if used alone to detect clinically important brain injury, were 16.7% (95% CI 4.7% to 37.4%) and 88.5% (95% CI 85.2% to 91.3%), respectively. Conclusion: Plasma S100B protein level was not associated with clinically significant intracranial lesion in patients with mTBI.